Influência da vazão de ar e da concentração inicial de nitrogênio no processo de nitrificação em um reator em batelada seqüencial com biomassa - Andrade, Lidiana de (2008)
Effluents from fish slaughterhouse are rich in nutrients, among other there is nitrogen that causes eutrophication in rivers. Nitrogen removal can be done in two parts: Nitrification and Denitrification. Nitrification is influenced by factors such as temperature, pH, alkalinity, C/N relation and other. This experiment aimed to test the influence of air flow and ammonia concentration in nitrification process in a sequential batch reactor with immobilized biomass. The reactor had volume of 2.5L, it was operated as rotational central composed design (DCCR), which were tested the factors: air flow (1 to 3L.min-1), initial concentration of ammonia nitrogen (40 to 100mgN.L-1). The results evaluated were conversion rate of ammonia to nitrate, nitrite percentage of accumulation, and capacity of microorganisms detention. The results showed with confidence interval of 95%, that the concentrations decrease of evaluated factors significantly increased the conversion percentage of ammonia to nitrate. The nitrite percentage of accumulation was influenced significantly by the increasing concentration of ammonia. And the biomass capacity of detention has not suffered significant influence from any factors considered.